The political idea of Julius Nyerere : a pan-Africanist project revisited - (:unkn) unknown (My University, 2017)
This dissertation revisits the history of the pan-Africanist project within the scope of the current intellectual trend, whose aim is to find appropriate solutions to tackle the problems of African nations in the globalized economy of today. It presents some African political figures whose ideas have shaped the history of Pan-Africanism while focusing more particularly on the theories of Julius Nyerere (1922-1999), a great pan-Africanist still out of the limelight. It also demonstrates how in the context of the current leadership crisis in Africa these ideas can contribute to a revival of Pan-Africanism. This dissertation however is neither a study of the policies implemented by Nyerere in Tanzania between 1960 and 1985 nor a rewriting of the history of Pan-Africanism itself. Its only aim is to contribute to the ongoing intellectual movement of activists and theorists of Pan-Africanism who are committed to building a comprehensive pan-Africanist policy. This study is based on the analysis of a programme of concrete transatlantic pan-Africanist solidarity designed by an Afro-American association named Pan-African Sills Project in the early 1970 relying on the vision of Julius Nyerere in order to support his efforts for the development of Tanzania.
Keywords: African Research